The Symmetry Concept of the Basic Education Teachers - Angela Couto; Cláudia Maia-Lima (European Teacher Education Network, 2016)
The curricular changes that have occurred with the Mathematics syllabus of 2007 and 2013 showed, among other situations, the introduction of new contents and the conceptual change of symmetry. For the teachers, these changes require scientific updates to be provided so that the outcomes of the mathematics teaching can be guaranteed. In the academic year 2011/2012 a questionnaire was applied to a 142 inservice basic education teachers of a particular region of Portugal, to analyze the content knowledge in this subject (symmetry) and the form of scientific update occurred. In this article we will make a description of those results.